Original articleIgG4-related inflammatory orbital pseudotumors – a retrospective case series - Oles, Krzysztof; Szczepanski, Wojciech; Skladzien, Jacek; Okon, Krzysztof; Leszczynska, Joanna; Bojanowska, Emilia; Bialas, Magdalena; Wrobel, Agnieszka; Mika, Joanna (Folia Neuropathologica, 2015)
Orbital diseases may be divided into congenital defects of the orbit, infectious and inflammatory diseases, orbital tumors (including malignant and benign tumors) and injuries. Idiopathic inflammatory syndromes are often encountered within the orbit and are usually classified as orbital pseudotumors. The etiology of pseudotumors of the vision organ is unknown. Infectious agents, autoimmune disorders and improper healing are taken into consideration in the pathogenesis of this disorder. Thanks to detailed studies conducted in recent years, a new disease syndrome was identified in 2001. It is known as IgG4-related disease, and its differentiation is based on the analysis of IgG4 levels in the affected tissues. Orbital locations of the disease were first reported in Japan as late as at the end of 2009. This finding triggered the European studies on this subject. To date, no such studies have been conducted in Poland. The starting study population consisted of 167 patients with isolated infiltrative tumor diseases within the orbital region treated at the Department of Otolaryngology, Head and Neck Surgery of the Medical College Jagiellonian University in Krakow. Detailed analysis and diagnostic screening for IgG4-related disease was performed in a total of 17 patients diagnosed with orbital pseudotumor.